From Liberal to Social Vision of Human Rights: The Innovative Contribution of Socialism to Social and Economic Rights - Vilanculo, Anselmo (Advances in Social Sciences Research Journal, 2022)
Liberalism and Socialism as well as the contribution of Socialism to Social and Economic Rights (SER) is explored. Enjoyment of Human Rights in different milieus is a result of differences between Liberal and Social understanding and approaches of Human Rights. Liberal approaches founds their roots in the Enlightenment movement and values of nation-state, rights to life, freedom of expression, civil liberty and property. Socialism has its foundations in the Marxist theories. Social relativism and relativism of rights challenges the Liberal universalism of rights. In Socialism, Social and Economic Rights are emphasized. Both Liberalism and Socialism have strengths and weaknesses. As so, the future of Human Rights depends on the combination of approaches, complementarities and synergies, which will result in a multiplicity and plurality of approaches toward Human Rights protection and promotion.